Tim-3-targeted vaccines overcome tumor immunosuppression and reduce cDC1 dependence to elicit potent anti-tumor immunity - Chunmei Fu; Tianle Ma; Björn E. Clausen; Ira Mellman; Aimin Jiang (Proceedings of the National Academy of Sciences, 2026)
Conventional type 1 dendritic cells (cDC1s) are specialized for cross-presenting tumor antigens and determining the efficacy of immunotherapies, including immune checkpoint blockade and adoptive cell therapy. However, their rarity and tumor-induced dysfunction severely limit CD8 T cell priming and represent a central bottleneck to therapeutic efficacy. While strategies such as anti–DEC-205-mediated antigen delivery and Flt3L-driven DC expansion can enhance host DC function, their reliance on functional cDC1s remains a significant constraint. We developed Tim-3-targeted vaccines by conjugating tumor antigens or neoantigens to anti–Tim-3 antibodies. These vaccines delivered antigens to both cDC1s and cDC2s, and elicited robust, durable CD8 T cell responses. Remarkably, Tim-3-targeted vaccines endowed cDC2s with efficient cross-presentation capacity that matched that of cDC1s. In tumor-bearing mice or in CD11c-β-catenin active mice, which model β-catenin-driven DC dysfunction, Tim-3-targeted vaccination restored cross-priming and counteracted tumor- and DC-mediated immunosuppression. In Batf3 −/− mice lacking cDC1s, anti-Tim-3-based vaccines still elicited significant CD8 T cell cross-priming and tumor control—albeit both were reduced compared to wild-type mice— demonstrating that cDC1s contribute to but are not essential for Tim-3-targeted vaccine–induced CD8 T cell priming and anti-tumor efficacy. Strikingly, a single dose of anti-Tim-3–neoantigen vaccination eradicated large established MC38 tumors in a CD8 T cell–dependent manner. Together, these data identify Tim-3-targeted vaccines as a next-generation cancer vaccine platform that broadens DC engagement, reduces reliance on cDC1s, and overcomes tumor- and DC-mediated immunosuppression, addressing key limitations of current DC-based cancer vaccines.